Damping modification factor based on random vibration theory using a source-based ground-motion model. Issue 136 (September 2020) - Zhang, Haizhong; Zhao, Yan-gang
Abstract: Damping modification factor (DMF) plays an important role in seismic design and hazard analysis. Many studies have dedicated to the DMF, but the existing formulations still show a quite large scatter. This study proposes a new theoretical approach for analyzing the DMF. The proposed approach models the seismic ground motion with a source-based Fourier amplitude spectrum (FAS) and estimates the DMF from the FAS based on random vibration theory. Using the proposed approach, the characteristics of the DMF are explored and explained. It is found that trends in the DMF with variation of the structural period and seismological parameters are mainly controlled by the shape of the FAS. The overall shapes of the DMF and FAS are almost symmetrical with respect to the period axis. When the shape of the FAS changes with seismological parameters, the DMF changes accordingly, and their shapes nearly always remain symmetrical. Highlights: A new theoretical approach for analyzing the damping modification factor (DMF) is developed. Using the proposed approach, the characteristics of the DMF are explored and explained. The trends in the DMF with variation of the seismological parameters are mainly controlled by the shape of the FAS. The overall shapes of the DMF and FAS are almost always symmetrical with respect to the period axis.